A study of principals’ perceptions of competence in common administrative roles - Glodt, Kelly J. (Kansas State University, 2006)
The Study of Principals’ Perceptions of Competence in Common Administrative Roles is quantitative. All Kansas principals were surveyed using the Principal’s Perception of Competence Survey, an instrument developed by the researcher, to gather the quantitative data. The issues surrounding the principalship are varied and complex. Many researchers would contend that building principals and the leadership they provide have more impact on school effectiveness than any other person or program. Whether they are beginning or experienced administrators, research suggests that principals must feel confident in their abilities if they are to be effective and make a strong impact on effective school functioning. The current and future shortage of quality principals is well documented. The present study was designed to identify common administrative roles and responsibilities in which beginning and experienced principals lack competence. In particular, the study identifies and addresses areas in which additional preparation and training of principals should be dedicated, which will assist preparatory programs and school districts. The results of this study will assist professors in university-based leader preparation programs, school district superintendents, and other school district personnel in developing university and site-based programs of preparation and support designed to retain quality school leaders. The findings of the study are organized around three research questions throughout Chapters IV and V. Discussions of the findings, as well as recommendations for future studies are also organized around the research questions.
Keywords: Principal competence; Administrative roles; Kansas principals; Education, Administration (0514)